Rapid synthesis of citrate-zinc substituted hydroxyapatite using the ultrasonication-microwave method. Issue 16 (November 2017) - Zhong, Zhenyu; Qin, Jinli; Ma, Jun
Abstract: Bio-inspired citrate-hydroxyapatite (HAP) nanoparticles doped with zinc ions were prepared from mussel shells via a rapid method of ultrasonication and microwave irradiation. It was found that zinc ions can interact with citrate ions in the crystallization process of HAP. The growth of nanocrystals in citrate solution was slower than that in HCl solution. The addition of zinc ions reduced the residue of citrate in the products and increased the crystallinity of HAP. Furthermore, mineral platelets with the length of 29 ± 7 nm and the thickness of 3–5 nm were obtained for Zn/(Zn+Ca) = 5 mol%, which displayed similar morphology with HAP platelets in bone. Moreover, the obtained HAP nanoparticles are promising for use as bone graft materials in biomedical applications.